Professional identification in the beginning of a teacher’s career: a longitudinal study on identity formation and the basic psychological need for autonomy in VET teacher training - Weiß, Julia Katharina [Verfasser]; Bottling, Matthias [Verfasser]; Kärner, Tobias [Verfasser] (My University, 2023)
„Introduction: This study examines the extent to which VET trainee teachers’ identification with their profession is related to their basic psychological need for autonomy and whether this is reflected in their intention to stay in the field. Trainee’s subjective experience of their professional identity interacts with different conditions of the training environment, whereby we focus on perceived autonomy support and autonomy thwarting behavior of seminar teachers. Methods: On the basis of a longitudinal design with a total of 79 trainee teachers in Germany and four survey time points during teacher training, corresponding developmental processes were traced over a total period of 1 year. Cross-lagged panel analyses allow us to draw conclusions about the extent to which professional identification of trainees interacts with autonomy-support or autonomy-thwarting conditions originating from seminar teachers and to what extent the aforementioned factors in turn affect intention to stay. Results: Cross-lagged panel analyses show that professional identification after 6 months in teacher training significantly predicts the intention to stay in the teaching profession half a year later. Significant cross paths each describe positive effects between professional identification and autonomy support and negative effects between professional identification and autonomy thwarting. Discussion: Particularly against the background of the shortage of teachers in Germany and other countries, the promotion of professional identification processes in the sense of a teacher identity can be assessed as crucial. In this respect, an autonomy-supporting environment, e.g., created by seminar teachers, can already contribute to that during teacher training.“ (authors‘ abstract; BIBB-Doku)
Keywords: P 3.2.3 Lehrer; S 1.4 Hochschulbildung; G 2.4.4 Biografiegestaltung; 370; Berufsschullehrer; Lehrerausbildung; Studium; Identitätsbildung; Berufliche Identität; Berufliche Autonomie; Beruflicher Verbleib; Einflussfaktor